ARTIFICIAL INTELLIGENCE-BASED SMART LEARNING MANAGEMENT IN STRENGTHENING ENGLISH LANGUAGE COMPETENCIES OF MADRASAH STUDENTS - Dewi Anizah; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The rapid development of Artificial Intelligence (AI) has transformed education toward more adaptive, personalized, and technology-driven learning systems. This study aims to analyze the concepts, implementation, opportunities, and challenges of AI-based smart learning management in strengthening the English language competence of madrasah students. This research employed a qualitative approach using a library research method. Data were collected from national and international journal articles, books, and other relevant scholarly sources. Data were analyzed through content analysis, including data reduction, categorization, interpretation, and conclusion drawing. The findings indicate that AI-based smart learning management enhances English language learning through personalized instruction, instant feedback, adaptive learning, and broader access to digital learning resources. AI technologies such as ChatGPT, speech recognition systems, intelligent tutoring systems, and adaptive learning platforms support the improvement of listening, speaking, reading, and writing skills. Effective implementation requires the integration of educational management functions, including planning, organizing, actuating, and controlling, supported by teacher competence, digital infrastructure, and institutional policies. Despite challenges related to digital literacy, human resource readiness, and ethical concerns, AI has significant potential as an innovative instrument for improving English language learning in madrasahs.